Sorbents for Extracorporeal Removal of Toxic Substances and Molecules with Adverse Biological Activity (Review) - A. S. Morozov; I. V. Bessonov; A. V. Nuzhdina; V. M. Pisarev (Общая реаниматология)
The review devoted to sorbents and sorbentbased medical devices used in clinical practice for extracorporeal detoxification using a hemoperfusion technique. Clinical data have confirmed the effectiveness of this approach for removal of bacterial endotoxins, lowdensity lipoproteins, and bilirubin. Other studies demonstrated successful application of sorbents to treat autoimmune diseases. Special attention is paid to hemoperfusion in as a possible treatment for severe sepsis and septic shock. The review justifies importance of development and application of novel multimodal sorbents, which combine both properties of selective and nonselective sorbents. The review discusses clinical efficacy of hemoperfusion and key molecular interactions between the sorbent and circulating molecules pathogenetically relevant to developing critical illness and severe diseases. The reference list: 137.